Encounters with Jesus : The Man in His Place and Time - Destro, Adriana (Book collections on Project MUSE., 2012)
"What was there in Jesus' person, behavior, and words that prompted not only much enthusiasm but also much hostility? This compelling portrait of the man Jesus of Nazareth by two pioneers of the anthropological study of early Christianity answers this vital question. They bring the fruit of years of scholarship to bear on a radical figure in Roman Galilee and on his encounters with others and the movement those encounters inspired. They give close attention to the everyday realities that shaped those encounters: the facts of travel, common meals, domestic space, and the interactions of bodies. The result is a refreshing new look at the man who proved so significant-and so controversial-in Western culture"--Publisher description